2021
DOI: 10.3389/fimmu.2021.773853
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Persistent Hypogammaglobulinemia More Than 10 Years After Rituximab Given Post-HSCT

Abstract: Rituximab (RTX) is an anti-CD20 monoclonal antibody that targets B cells—from the immature pre-B-cell stage in the bone marrow to mature circulating B cells—while preserving stem cells and plasma cells. It is used to treat autoimmune diseases, hematological malignancies, or complications after hematopoietic stem cell transplantation (HSCT). Its safety profile is acceptable; however, a subset of patients can develop persistent hypogammaglobulinemia and associated severe complications, especially in pediatric po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Once the patient received rituximab, low B cells and hypogammaglobulinemia persisted thus making difficult to establish an appropriate diagnosis of CVID. It is well described that rituximab may cause long term immunological effects undistinguishable from CVID in susceptible individuals specially with low IgG and IgA levels before therapy (23,24). Therefore, the role of NFKB1 as either causative or predisposing gene in this patient remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…Once the patient received rituximab, low B cells and hypogammaglobulinemia persisted thus making difficult to establish an appropriate diagnosis of CVID. It is well described that rituximab may cause long term immunological effects undistinguishable from CVID in susceptible individuals specially with low IgG and IgA levels before therapy (23,24). Therefore, the role of NFKB1 as either causative or predisposing gene in this patient remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…[43] We also identi ed a total of 4 patients with a post-RTX class-switch recombination-de ciency, a phenomenon that has only recently emerged in literature and been described as profoundly rare. [11,35,38,44,45] A recent study by De Bruin et al showed that an impaired IgG + memory B cell maturation post-RTX could not be attributed to intrinsic B cell defects, as in vitro stimulation led to normal maturation and class-switch recombination abilities [42].…”
Section: Discussionmentioning
confidence: 99%
“…While hypogammaglobulinemia following biologic B-cell targeting therapies might be regarded as an uncommon but expected iatrogenic effect, it is significantly more challenging to establish the pathogenetic role of B-cell perturbation in patients that present a prolonged persistence of B-cell aplasia and low Ig values [8,9,11,17,23,29]. The lack of proper pretreatment assessment contributes to this confusion when hypogammaglobulinemia persists for years after treatment and selective B-cell targeting might not be sufficient to explain the lack of immune recovery.…”
Section: Risk Of Underlying Primary Immune Deficiencymentioning
confidence: 99%
“…Also, post-RTX PH has been observed in patients with HIV-associated lymphomas [23] and in patients after high-dose chemotherapy [24,25] as well as after stem cell transplant [14,[26][27][28]. Specifically, post-transplant EBV-associated lymphoproliferative disorder seems to be a high-risk condition for prolonged post-RTX hypogammaglobulinemia [29,30]. A higher number of doses have been significantly associated with PH in patients with NHL [24,31] by different groups, although data remain scarce and mainly retrospective.…”
Section: Malignant Disorders and Transplant Recipientsmentioning
confidence: 99%